Oxides for Pt Capture in the Ammonia Oxidation Process—A Screening Study - Julie Hessevik; Cathinka S. Carlsen; Oskar K. Bestul; David Waller; Helmer Fjellvåg; Anja O. Sjåstad (Reactions)
Metallic Pd/Ni gauzes, located downstream of the Pt/Rh ammonia oxidation catalyst nets in the Ostwald process, is the current technology for capturing volatile gas phase platinum and rhodium species lost from the Pt/Rh combustion catalyst through evaporation. In this screening study, we explore four oxide families, ABO3 perovskites, (ABO3)n(AO) Ruddlesden–Popper (RP) phases, AO rock salt, and A2O3 sesquioxide type oxides, as alternative materials for platinum capture. It was found that all the tested nickelates, LaNiO3, NdNiO3, La2NiO4, and La4Ni3O10, captured platinum well and formed A2NiPtO6. In contrast, La0.85Sr0.15FeO3, LaFeO3, and LaCoO3 did not capture platinum. CaO, SrO, and Nd2O3 formed low-dimensional platinates such as CaxPt3O4, Sr4PtO6, and a newly discovered neodymium platinate, Nd10.67Pt4O24. Gd2O3 did not capture platinum in bench-scale experiments in dry air, but did, however, seem to capture platinum under pilot plant conditions, likely due to the co-capture of Co lost from the N2O abatement catalyst. The catalytic activity of both oxides and platinum-containing products were studied, toward NOx and N2O decomposition. None of the oxides showed significant activity toward NOx decomposition, and all showed activity toward N2O decomposition, but to different extents. An overall assessment of the screened oxides with respect to potential use in industrial Ostwald conditions is provided. All tested oxides except CaO and SrO withstood industrial conditions. From our assessments, the nickelates and A2O3 (A = Nd, Gd) stand out as superior oxides for platinum capture.